Information Technology and Economic Change: The Impact of The Printing Press * - Dittmar, Jeremiah E. (Quarterly Journal of Economics, 2011)
The printing press was the great innovation in early modern information technology, but economists have found no macroeconomic evidence of its impact. This article exploits city-level data. Between 1500 and 1600, European cities where printing presses were established in the 1400s grew 60% faster than otherwise similar cities. Cities that adopted printing in the 1400s had no prior advantage, and the association between adoption and subsequent growth was not due to printers choosing auspicious locations. These findings are supported by regressions that exploit distance from Mainz, Germany–the birthplace of printing–as an instrument for adoption. Copyright 2011, Oxford University Press.